Efektivitas Konten Motivasi Youtube GreatMindIndonesia On Marissa’s Mind dalam Meningkatkan Semangat Hidup Penonton - Cantika Najla Thifaliawan; Novie Susanti Suseno; Resty Mustika Pratiwi (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine in depth the effectiveness of motivational content On Marissa's Mind on the YouTube channel GreatmindIndonesia in increasing the enthusiasm for life of its viewers. This study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, documentation, and literature studies. The informant in this study was an active  viewer of YouTube motivational content, while the expert resource person was a counselor, writer, and psychologist who has competence in the field of mental health. Viewers reported that this show had a positive impact on their mindset and enthusiasm in living life, especially in facing life challenges such as stress due to work, financial problems, and searching for identity. Through qualitative analysis techniques on viewer comments and in-depth interviews, it was found that the style of content delivery that is empathetic and relevant to everyday life is the key to the success of this content in influencing its audience. This content not only functions as a motivational medium, but also as a means of education and self- reflection for individuals who are struggling to improve their quality of life and mental health. With a strong narrative approach and based on real experiences, the content of On Marissa's Mind has been proven to have a significant influence on the enthusiasm for life of its viewers.